Characterization of Remote Sensing Albedo Over Sloped Surfaces Based on DART Simulations and In Situ Observations. Issue 16 (27th August 2018) - Wu, Shengbiao; Wen, Jianguang; You, Dongqin; Hao, Dalei; Lin, Xingwen; Xiao, Qing; Liu, Qinhuo; Gastellu‐Etchegorry, Jean‐Philippe
Abstract: In situ albedo measurement over sloped surfaces is pivotal to a wide range of remote sensing applications, such as the estimation and evaluation of surface energy budget at regional and global scales. However, existing albedo measurements over rugged terrain are limited and controversial and remain a major challenge. In this paper, two commonly measured broadband albedos, which depend on incoming/outgoing geometric conditions, were characterized over sloped surfaces and illustrated. These albedos are the horizontal/horizontal sloped surface albedo (HHSA) and inclined/inclined sloped surface albedo (IISA). The 3‐D Discrete Anisotropic Radiative Transfer (DART) model simulations over varying slopes were utilized to quantify differences in the albedos. In particular, the effects of the slope, aspect, the solar zenith angle, and the proportion of diffuse skylight were investigated. The results show that absolute (relative) biases between HHSA and IISA are significant, reaching up to 0.026 (61.8%), 0.134 (62.4%), and 0.114 (62.3%) in the visible, near‐infrared, and shortwave broadbands, respectively. In addition, the diurnal cycle differences between HHSA and IISA were also compared using DART simulations and in situ observations over four typical slopes. Comparisons reveal that topographic parameters (e.g., slope and aspect) and atmospheric conditions (e.g., diffuse skylight and atmospheric visibility) are the primary factors, while the optical and structural parameters have a smaller effect. Key Points: Albedo measurements over sloped surfaces are significantly affected by the radiometer orientation Two commonly measured sloped surface albedos were characterized and analyzed using 3‐D Discrete Anisotropic Radiative Transfer (DART) simulations and in situ observations over four typical slopes Both topographic parameters and atmospheric conditions affect the patterns of the horizontal and slope‐parallel measured broadband albedos; using the DART simulations over different slopes, the absolute (relative) bias values between these two albedos can be up to 0.026 (61.8%), 0.134 (62.4%), and 0.114 (62.3%) in the visible (VIS), near‐infrared (NIR), and shortwave (SW) bands, respectively